The effect of strategic leadership in achieving excellence performance - Akram Mohsen Al-Yasiri; Suadad Ali Abed ALabbas (Iraqi Journal for Administrative Sciences, 2024)
The present study aimed to test the effect of strategic leadership through its dimensions (a focus on the customer, operational efficiency, business development, organizational innovation) based on (Duursema, 2013:58) In the Excellence performance by its dimensions (process and service results, the results of a focus on the customer, the results of a focus on human resources, the results of the budget and financial market outcomes) based on (Baldrige Performance Excellence Program, 2015:26) of the working individuals in the satellite channel Karbala and they are study sampl numbered (165) individuals by using the (Questionnaire Form) designed for this purpose and analyzing the obtained and statistically processed data. And the research adopted using some statistical methods to achieve the most important and related results (confirmatory factor analysis, Rank Correlation Coefficient (Spearman), standard deviation, T test, simple correlation coefficient, and regression analysis) used by statistical program (Spss V.15;Amose V.21) and the results proved that the hypotheses are correct. The study found several conclusions the most important of it (an association and effect relationship with moral significant within variables of the study). And presents a set of recommendations that related to its variables, The most prominent of them is that the researched organization should recognize the role and importance of strategic leadership in shaping its directions in order to achieve its goals for survival, growth and facing the challenges in the long term in order to achieve excellence performance in front of its competitors.